2016
DOI: 10.1117/12.2241198
|View full text |Cite
|
Sign up to set email alerts
|

Internal solitons in the Andaman Sea: a new look at an old problem

Abstract: When Osborne and Burch [1] reported their observations of large-amplitude, long internal waves in the Andaman Sea that conform with theoretical results from the physics of nonlinear waves, a new research field on ocean waves was immediately set out. They described their findings in the frame of shallow-water solitary waves governed by the K-dV equation, which occur because of a balance between nonlinear cohesive and linear dispersive forces in a fluid. It was concluded that the internal waves in the Andaman Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…In this map, only the leading and strongest observations were accounted for, and the mean distance between mode-2 ISW-like packet envelopes in each image (λ) was also listed in Table 1, along with their corresponding number of observations (N WT ). It is worthwhile noting that these features consistently present interpacket distances of around 30 km, just as is observed in our case study in Figure 3b and in da Silva and Magalhaes [22]. Also, the composite map in Figure 1 reveals a well-organized IW field whose propagation envelope (in light red in Figure 1) is fairly along the tidal currents there, and suggests an origin along the shallow ridges to the west.…”
Section: Sar Observationssupporting
confidence: 82%
See 2 more Smart Citations
“…In this map, only the leading and strongest observations were accounted for, and the mean distance between mode-2 ISW-like packet envelopes in each image (λ) was also listed in Table 1, along with their corresponding number of observations (N WT ). It is worthwhile noting that these features consistently present interpacket distances of around 30 km, just as is observed in our case study in Figure 3b and in da Silva and Magalhaes [22]. Also, the composite map in Figure 1 reveals a well-organized IW field whose propagation envelope (in light red in Figure 1) is fairly along the tidal currents there, and suggests an origin along the shallow ridges to the west.…”
Section: Sar Observationssupporting
confidence: 82%
“…This is somewhat unexpected since the larger mode-1 ISW packets commonly observed in the Andaman Sea are known to be more frequently observed close to spring tides (see e.g., [13]). For consistency, one other image which is presented in da Silva and Magalhaes [22] is also presented in Table 1, and contains a very similar picture to that in Figure 3b.…”
Section: Sar Observationsmentioning
confidence: 81%
See 1 more Smart Citation
“…A high-resolution non-hydrostatic and fully nonlinear setup is used in the MITgcm to simulate the internal wave field along the Ten-Degree Channel of the Andaman Sea. Previous studies 12,13 revealed the propagation of unusually long-lived mode-2 solitary-like waves along this particular stretch, whereas the usual large-scale mode-1 ISWs were never observed in satellite imagery. The model results are consistent with these observations since they too feature high-frequency mode-2 oscillations propagating along the pycnocline instead of the usual mode-1 solitary waves.…”
Section: Discussionmentioning
confidence: 68%
“…The phase speeds estimated from satellite imagery by Tensubam et al [52] are in good agreement with phase speeds estimated from the Sturm-Liouville equation using climatological stratification and realistic bathymetry of the area. da Silva and Magalhaes [53] have estimated 2.37 m/s for the phase speed of mode-1 waves with interpacket distance of 106 km. Estimates from Sun [49] in the south Andaman Sea have provided values ranging from 2.35 to 2.65 m/s for the phase speed of long-lived mode-1 waves.…”
Section: Methodsmentioning
confidence: 98%